2018
DOI: 10.1002/cbic.201800093
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of Hyaluronic Acid Synthase from Pasteurella multocida towards High‐Molecular‐Weight Hyaluronic Acid

Abstract: Hyaluronic acid (HA), with diverse cosmetic and medical applications, is the natural glycosaminoglycan product of HA synthases. Although process and/or metabolic engineering are used for industrial HA production, the potential of protein engineering has barely been realised. Herein, knowledge-gaining directed evolution (KnowVolution) was employed to generate an HA synthase variant from Pasteurella multocida (pmHAS) with improved chain-length specificity and a twofold increase in mass-based turnover number. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…For example, sucrose enhances the stability of some enzymes significantly [31]. Protein engineering could also help to improve stability or other characteristics as it was recently shown that a PmHAS variant with better activity and chain length specificity was created [57].…”
Section: Resultsmentioning
confidence: 99%
“…For example, sucrose enhances the stability of some enzymes significantly [31]. Protein engineering could also help to improve stability or other characteristics as it was recently shown that a PmHAS variant with better activity and chain length specificity was created [57].…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the balance between screening efforts and gained molecular understanding, KnowVolution enables the tailoring of protein properties with minimal experimental efforts through the integration of directed evolution and computational analysis in four phases. More than ten KnowVolution success stories have been reported for diverse protein properties, for instance, to increase cellobiose activity of an aryl sulfotransferase, to improve the polypropylene binding of a polymer‐binding peptide, or to improve the chain‐length specificity of a hyaluronic acid synthase . Herein, we report the first laccase KnowVolution campaign toward increased tolerance at alkaline pH (pH≥9.0).…”
Section: Introductionmentioning
confidence: 99%
“…474 Hyaluranon synthase has also be engineered for improved turnover and an increase in the molecular weight of the acid produced. 475…”
Section: Humectants and Emollientsmentioning
confidence: 99%